Patterns of ecological specialization among microbial populations in the Red Sea and diverse oligotrophic marine environments. Issue 6 (11th May 2013) - Thompson, Luke R.; Field, Chris; Romanuk, Tamara; Kamanda, David; Siam, Rania; El, Hamza; Stingl, Ulrich
Abstract Large swaths of the nutrient‐poor surface ocean are dominated numerically by cyanobacteria (Prochlorococcus), cyanobacterial viruses (cyanophage), and alphaproteobacteria (SAR11). How these groups thrive in the diverse physicochemical environments of different oceanic regions remains poorly understood. Comparative metagenomics can reveal adaptive responses linked to ecosystem‐specific selective pressures. The Red Sea is well‐suited for studying adaptation of pelagic‐microbes, with salinities, temperatures, and light levels at the extreme end for the surface ocean, and low nutrient concentrations, yet no metagenomic studies have been done there. The Red Sea (high salinity, high light, low N and P) compares favorably with the Mediterranean Sea (high salinity, low P), Sargasso Sea (low P), and North Pacific Subtropical Gyre (high light, low N). We quantified the relative abundance of genetic functions among Prochlorococcus, cyanophage, and SAR11 from these four regions. Gene frequencies indicate selection for phosphorus acquisition (Mediterranean/Sargasso), DNA repair and high‐light responses (Red Sea/Pacific Prochlorococcus), and osmolyte C1 oxidation (Red Sea/Mediterranean SAR11). The unexpected connection between salinity‐dependent osmolyte production and SAR11 C1 metabolism represents a potentially major coevolutionary adaptation and biogeochemical flux. Among Prochlorococcus and cyanophage, genes enriched in specific environments had ecotype distributions similar to nonenriched genes, suggesting that inter‐ecotype gene transfer is not a major source of environment‐specific adaptation. Clustering of metagenomes using gene frequencies shows similarities in populations (Red Sea with Pacific, Mediterranean with Sargasso) that belie their geographic distances. Taken together, the genetic functions enriched in specific environments indicate competitive strategies for maintaining carrying capacity in the face of physical stressors and low nutrient availability.